The Influence of Timeliness in Digital Financial Reporting (E-Reporting) on Market Reaction at the Indonesia Stock Exchange: The Mediating Role of Information Asymmetry - Gracesiela Yosephine Simanjuntak; Rimky Mandala Simanjuntak; Apriani Magdalena Sibarani; Rike Yolanda Panjaitan; Ivo Maelina Silitonga (Program Studi Akuntansi Universitas Simalungun, 2025)
This research investigates how digital financial reporting timeliness (e-reporting) influences market reactions in the Indonesia Stock Exchange through reduced information asymmetry mechanisms. Drawing upon signaling theory, market efficiency theory, and information asymmetry theory, this study examines how timely electronic disclosure practices create value through improved market responsiveness and reduced uncertainty among investors. Using Structural Equation Modeling with Partial Least Squares (PLS-SEM) analysis on 145 publicly listed companies in Indonesia (725 firm-year observations, 2019-2023), the research demonstrates that e-reporting timeliness significantly reduces information asymmetry (β = -0.683, p < 0.001) and positively influences market reactions (β = 0.534, p < 0.001). Information asymmetry substantially mediates the relationship between e-reporting timeliness and market reactions (indirect effect = 0.421, p < 0.001, VAF = 44.1%). The model explains 62.8% of information asymmetry variance and 58.3% of market reaction variance. This study provides comprehensive empirical evidence of how digital reporting infrastructure transforms capital market efficiency and investor decision-making processes in emerging market contexts